Intestinal macrophages in mucosal immunity and their role in systemic lupus erythematosus disease. (October 2018) - Pan, F; Tang, W; Zhou, Z; Gilkeson, G; Lang, R; Jiang, W
Monocytes play an important role in inducing host systemic immunity against invading pathogens and inflammatory responses. After activation, monocytes migrate to tissue sites, where they initiate both innate and adaptive immune responses, and become macrophages. Although mucosal macrophages produce inflammatory cytokines in response to pathogens, the perturbations in innate immune signaling pathway have been implicated in autoimmune diseases such as systemic lupus erythematosus (SLE). In this review, we focus on the role of human macrophages in intestinal innate immune responses, homeostasis, and SLE disease. We further discuss sex differences in the intestinal macrophages and their role in the physiology and pathogenesis of SLE.